Triggers, templates and twitches in the tracking of emerging strategic issues - Sawy, Omar A. El; Pauchant, Thierry C. (Strategic Management Journal, 1988)
Abstract A longitudinal investigation of group tracking of potential new applications and markets created by an emerging technology (cellular telephones) is used to gain more understanding of the shifts of cognitive frames of reference in the environmental tracking of emerging strategic issues. The dynamics of frame of reference shifts is examined through the derivation and operationalization of the concepts of templates, triggers and twitches. The results posit that examining the frame of reference shifts can be more informative than examining the frames themselves. Implications for strategic management practice and research are addressed.